2019
DOI: 10.29202/nvngu/2019-1/19
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of social capital as a positive externality of corporate social responsibility development in transition economies

Abstract: ACCuMulAtion of SoCiAl CAPitAl AS A PoSitiVe externAlitY of CorPorAte SoCiAl reSPonSiBilitY deVeloPMent in trAnSition eConoMieS Purpose. Justification of a hypothesis about positive externality of involvement of companies in projects of corpo rate social responsibility that is connected with development of the relations of trust and accumulation of the social capital at the level of separate enterprises and national economy in general. An important aspect of the research is determination of impact of social re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…Thus, according to the data presented in Figure 5, there is a direct correlation between the level of gov-ernment social expenditures (% of GDP) and the level of social capital accumulation. At the same time, as our previous research showed, the development of CSR is also an important factor in social capital accumulation, through the creation and promotion of trustful relationships among stakeholders (Bazylevych et al 2019). Corporate social responsibility implies business responsibility in four main areas: economic (the production of goods and services that are demanded by society), legal (the functioning of business in accordance with current legislation), ethical (the protection of the rights of employees, consumers and other stakeholders beyond the requirements stipulated by law) and voluntary (business response to the expectations and social needs of society, addressing such global social problems as poverty, hunger, and discrimination) (Carroll 1979).…”
Section: Crisis Of the Welfare Statementioning
confidence: 76%
“…Thus, according to the data presented in Figure 5, there is a direct correlation between the level of gov-ernment social expenditures (% of GDP) and the level of social capital accumulation. At the same time, as our previous research showed, the development of CSR is also an important factor in social capital accumulation, through the creation and promotion of trustful relationships among stakeholders (Bazylevych et al 2019). Corporate social responsibility implies business responsibility in four main areas: economic (the production of goods and services that are demanded by society), legal (the functioning of business in accordance with current legislation), ethical (the protection of the rights of employees, consumers and other stakeholders beyond the requirements stipulated by law) and voluntary (business response to the expectations and social needs of society, addressing such global social problems as poverty, hunger, and discrimination) (Carroll 1979).…”
Section: Crisis Of the Welfare Statementioning
confidence: 76%
“…According to the current studies, the efficiency of CSR also depends on other social, political, and economic factors, such as the level of corruption, Theoretical and methodological approaches to the formation of a modern system of national and international enterprises, organizations and institutions' development advancement of legislation system, violation of human rights, discrimination, macroeconomic and political instability, lack of social guarantees from the state, as mentioned weaknesses can reduce or eliminate the overall positive effect of CSR on the population wellbeing [9].…”
Section: Corporate Social Responsibility and Social Capital Creationmentioning
confidence: 99%
“…Moreover, current studies have shown that the process of transferring some social functions of the state as the protection of the rights and freedoms of citizens, health and social insurance, education and training to the private sector in the form of corporate social responsibility can improve the efficiency of public financial resources, and also contributes to the accumulation of human and social capital, which is a prerequisite for long-term economic growth of the country [9].…”
Section: The Link Between the Development Of Corporate Social Respons...mentioning
confidence: 99%
“…У цьому контексті слід зазначити, що основним результатом соціальної відповідальності бізнесу є нагромадження соціального капіталу, що проявляється як окремий ресурс та як засіб мобілізації необхідних ресурсів. Соціальний капітал як ресурс акумулюється в результаті: 1) побудови довірчих міжособистісних стосунків між працівниками, управлінцями і працівниками, власниками та управлінцями, представниками бізнесу, споживачами та представниками бізнесу; 2) формування соціальної мережі на основі персональних «зв'язків»; 3) залучення громадськості до вирішення спільних проблем; 4) формування та слідування загальноприйнятим соціальним нормам [1]. Отже, побудова довірчих відносин та очікування спільної вигоди сприяють постійності норм поведінки економічних суб'єктів без будь-якого інституційного або іншого мотиваційного механізму, що сприяє подальшій акумуляції соціального капіталу.…”
unclassified